PENGARUH OPERATING LEVERAGE TERHADAP POFITABILITAS (Pada Perusahaan Manufaktur Industri Barang Konsumsi) - S, Basir; Hasanah, Shofhatul Maulidiyah (IQTISHODUNA, 2017)
Abstract: The manufacturing company is an industrial company that processes raw materials into finishedgoods. In its operations, manufacturing companies require huge costs. Large-scale enterprise will easilyobtain a loan. However, with debt financing will affect the profitability of the company. The purpose of thisstudy was to determine the effect of operating leverage on profitability in the consumer goods industrymanufacturing company. The sample used in this study were 17 out of a population of 37 companiesmanufacturing consumer goods industry 2011-2015. The results showed that operating leverage effectsignificantly positively on profitability.